2001
DOI: 10.1021/jp003000u
|View full text |Cite
|
Sign up to set email alerts
|

Interfacial Recombination Processes in Dye-Sensitized Solar Cells and Methods To Passivate the Interfaces

Abstract: Conventional dye-sensitized solar cells function efficiently only with a single redox couple, I-/I2, because of the unusually slow kinetics for I2 reduction on SnO2 and TiO2 surfaces. When faster redox couples such as ferrocene/ferrocenium are employed, the rapid interfacial recombination of photoinjected electrons with the oxidized half of the redox couple eliminates the photovoltaic effect. To make use of other, perhaps more appropriate, redox couples in these cells, the interfacial recombination processes m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
512
0
4

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 499 publications
(528 citation statements)
references
References 48 publications
(70 reference statements)
12
512
0
4
Order By: Relevance
“…1c). 30,38,39 In our case we employ carboxylic acid (R-COOH) functionalized molecules, a commonly used binding group to TiO 2 . Once grafted to the semiconductor surface, the passivation of midgap states is observed as the Fermi level is shifted (see ESI S1 †).…”
Section: Sams To Passivate the Metal-semiconductor Interfacementioning
confidence: 99%
“…1c). 30,38,39 In our case we employ carboxylic acid (R-COOH) functionalized molecules, a commonly used binding group to TiO 2 . Once grafted to the semiconductor surface, the passivation of midgap states is observed as the Fermi level is shifted (see ESI S1 †).…”
Section: Sams To Passivate the Metal-semiconductor Interfacementioning
confidence: 99%
“…Wang and co-workers [42] reported prolonged electron lifetimes and increased Voc and Jsc by using CaCO3 for surface passivation. Gregg et al [8,43] formed a blocking layer on the mesoporous electrode after dye adsorption by a silanization treatment. Their aim was to block parts of the electrode not covered by the dye from the electrolyte so that they could use fast one-electron redox couples.…”
Section: Blocking Layermentioning
confidence: 99%
“…In order to retard the unexpected recombination, various technologies have been used, such as atomic layer deposition, to produce surface coatings onto the nanoporous films. But the results were not satisfied due to the dilemma of injection and recombination [31]. Very recently Daeneke et al [32] have reported a highly efficient DSC based on the Fc + /Fc couple in combination with a carbazole donor-acceptor organic dye.…”
Section: Transition Metal Complexes Systemsmentioning
confidence: 99%